Process improvement and organisational learning: evidence from engineering-oriented small and medium-sized enterprises - Matthews, Rupert Lawrence (2013)
Process improvement has been identified as a central topic of operations management, being relevant to the different functional areas and assisting in providing the benefits operations management aims to realise. While extensive research has been conducted on specific process improvement methodologies, high resource requirement of specific process improvement methodologies make them inappropriate for many Small and Medium Sized Enterprises (SMEs). Compared to specific improvement methodologies, organisational learning was identified as an appropriate theoretical perspective from which to analyse process improvement activities within SMEs, leading to the presentation of the following three research questions: How do engineering-oriented SMEs undertake process improvement? What is the applicability of the three models of organisational learning within engineering-oriented SMEs? How does organisational learning contribute to understanding of process improvement within engineering-oriented SMEs?